PEMENUHAN UNSUR PIDANA DALAM TINDAK PIDANA PENCEMARAN NAMA BAIK BERDASARKAN UNDANG- UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Anita Julianti; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Defamation criminal acts based on information media and electronic transactions are regulated in Article 27 paragraph (3) of Law Number 19 Year 2016 Amendment to Law Number 11 Year 2008 Regarding Information and Electronic Transactions. Humiliation and / or defamation are criminal acts that often occur polemics in today's society, especially in the field of information technology, which has an important role in the present. But along with this development, problems related to criminal defamation arose with the criminal element problem, which contained several cases of non-fulfillment of criminal defamation elements.This research uses the typology of normative legal research or so-called doctrinal legal research, which is more specifically discusses the principles of law. In this study the authors use the nature of descriptive research, because the authors describe the fulfillment of criminal elements in criminal defamation actions based on Law Number 19 Year 2016 Amendments to Law Number 11 Year 2008 Concerning Information and Electronic Transactions. The results of the research conducted by the author is in determining actions which are categorized as acts against the law, it means that prior formulation of acts that are prohibited by the law must be known, could be threatened with punishment if they contain the full offense when the offense arises is considered offense that is considered to have been fully carried out . In accordance with the formulation in the Law on Information and Electronic Transactions specifically in Article 27 paragraph (3) of Law Number 19 Year 2016 Amendment to Law Number 11 of 2008 Concerning Information and Electronic Transactions. Law Enforcement Officials are expected to understand in detail the fulfillment of the element of criminal defamation so that there is legal certainty and does not cause multiple interpretations Keywords: Criminal Act – Defamation – Information and Electronic Transaction